A Rare case of HUS and ADEM - Moghtaderi, Mastaneh; Rahimzadeh, Nahid; Eshaghi, Hamid; Shahrokhi, Amin; Mehrkash, Mehryar (Journal of Pediatric Nephrology, 2013)
A 3-year-old girl was admitted with typical hemolytic uremic syndrome (HUS) and conservative treatments were initiated. During hospitalization, she had seizures, right hemiparesis, and loss of consciousness. Initial MR of the brain showed changes of acute disseminated encephalomyelitis (ADEM). She was treated with intravenous methylprednisolone and immunoglobulin. Upon improvement of her clinical condition, she was discharged with oral prednisolone which was tapered after two months. After one year fallow-up, the child now has a normal renal function and normal neurodevelopment.